The Use of Semantic Mapping Strategy to Enhance EFL Students’ Vocabulary Mastery at The Seventh Grade of SMP Negeri 1 Tapa - Jihan Asfari Daud; Rasuna Rasid Talib; Fahria Malabar (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study explores the effectiveness of the Semantic Mapping strategy in enhancing vocabulary mastery among seventh-grade EFL students at SMP Negeri 1 Tapa. The research employed a quasi-experimental design with a pre-test and post-test to assess students’ vocabulary improvement. The participants were selected through purposive sampling from class 7-3, identified as having lower vocabulary proficiency. The intervention involved the implementation of Semantic Mapping in vocabulary lessons over a set period. The results showed a substantial improvement in students’ vocabulary scores, with the pre-test average at 46.36 and the post-test average increasing to 70.68. Statistical analysis using a paired sample t-test revealed a p-value of 0.000, indicating a statistically significant difference between pre-test and post-test scores. This confirms the rejection of the null hypothesis (H₀) and the acceptance of the alternative hypothesis (H₁), which states that the Semantic Mapping strategy positively affects vocabulary acquisition. The findings suggest that this strategy aids learners in organizing and retaining vocabulary more effectively. Therefore, it is recommended that English teachers incorporate Semantic Mapping into their instructional practices to enhance vocabulary development and support overall language learning success.